Perceptions of caregivers and adolescents of the use of telemedicine for the child sexual abuse examination. (November 2018) - Stavas, Natalie; Shea, Judy; Keddem, Shimrit; Wood, Joanne; Orji, Whitney; Cullen, Catherine; Scribano, Philip
Abstract: Background: Childhood sexual abuse is a common cause of morbidity and mortality. All victims should receive a timely comprehensive medical exam. Currently there is a critical shortage of child abuse pediatricians who can complete the comprehensive child sexual abuse examination. Telemedicine has emerged as an innovative way to provide subspecialty care to this population. Despite the growing popularity of telemedicine, no literature exists describing patient and caregiver perceptions of telemedicine for this sensitive exam. Objective: To explore caregiver and adolescent perspectives of the use of telemedicine for the child sexual abuse examination and discover factors that drive satisfaction with the technology. Participants and Setting: Caregivers and adolescents who presented for a child sexual abuse medical evaluation at our county's child advocacy center. Methods: We completed semi structured interviews of 17 caregivers and 10 adolescents. Guided by the Technology Acceptance Model interviews assessed perceptions about: general feelings with the exam, prior use of technology, feelings about telemedicine, and role of the medical team. Interviews were audio-recorded, transcribed, coded and analyzed using content analysis with constant comparative coding. Recruitment ended when thematic saturation was reached. Results: There was an overwhelming positive response to telemedicine. Participants reported having a good experience with telemedicine regardless of severity of sexual abuse or prior experience with technology. Behaviors that helped patients and caregivers feel comfortable included a clear explanation from the medical team and professionalism demonstrated by those using the telemedicine system. Conclusion: Telemedicine was widely accepted by adolescents and caregivers when used for the child sexual abuse examination.